Análise do desempenho do alimentador Palmital com o uso de seccionalizador visando a melhoria dos índices de continuidade de fornecimento de energia elétrica - Chan, Amanda Wen Quan (2013)
The concessionaires of electric energy distribution are evaluated by Aneel through the collective (DEC and FEC) and individuals (DIC, FIC and DMIC) continuity indicators. If these indicators exceed the established limit values, the electric power distributors are punished with fines. Therefore, it is growing the search for new technologies and tools that minimize the interruptions and its duration in way to improve the electricity supply quality. In this context, the sectionalizer is an equipment that allows the opening of an electric circuit in fault, enabling the differentiation of a transitory fault from a permanent one in order to isolate the faulty section. In this way, the power down of feeding system is avoided and a less number of consumers is affected. The purpose of this graduation conclusion work is to analyze the performance of the sectionalizer installed in the Palmital feeder from Pinhais set belonging to Copel, as a technical solution to reduce the power outage in the region and resulting reduction of the electric energy supply continuity indicators. For this analysis two situations were considered: one scenario before the Secc’s installation and the other scenario after this installation. This division was necessary to evaluate the evolution or not of DEC, FEC, DIC, FIC and DMIC due to the equipment’s installation.